Komposisi Jenis dan Kepadatan Rumput Laut Hydrokoloid berdasarkan Karakteristik Dasar Perairan di Daerah Intertidal Nusakambangan Timur Cilacap - Dwi Sunu Widyartini; Achmad Ilalqisny Insan; Kamsinah kamsinah (Fakultas Biologi Universitas Jenderal Soedirman, 2021)
ABSTRACT Hydrocolloid seaweed is seaweed which contains agar, carrageenan and alginate, which are widely used as industrial raw materials. This study aims to determine the type composition of hydrocolloid seaweed and its density based on the characteristics of the bottom waters in the intertidal area of ​​East Nusakambangan Cilacap. The waters of East Nusakambangan have a central coral beach and a hollow coral beach which has a substrate in the form of sand, coral, volcanic rock, and coral fragments. This study used a survey method and sampling using a transect, a perpendicular line of the coast towards the sea, each transect line was placed with a quadrant plot (1 x 1m2) randomly selected on hard and soft substrates. The results of this study, the coral substrate on the two beaches obtained 2-8 types of hydrocoloid seaweed, with the highest composition of seaweed species of 57.6% on hard substrate with the highest density in the Gracilaria gigas species; 440.6-1239.7 g / m2, Gracilaria gigas has a Dichotomus branching type with a cylindrical talus shape. In the mixed substrate on the coast of Karang Tengah, there were 4 types of Hydrocoloid seaweed with a composition of 46.3% hydrocoloid species with the highest density in the species Padina australis; 387.7g / m2. Padina australis sheet and unbranched talus form Keywords: hydrocolloid, composition, East Nusakambangan, Intertidal